Top-tier advisors in M&A transactions : they used to matter - Silva, Caio Leandro Oliveira Costa da (2016)
This master thesis investigates the effect of top-tier advisors on bidder returns, probability of completion and time to completion of M&A deals announced between January 1995 and December 2015. In this context, the fees received by top-tier advisors and their ability to identify and appropriate synergies are also subjected to study. Based on a sample of 6716 U.S. and cross border deals, we found that (1) after 2001 top-tier advisors are no longer associated with higher cumulative abnormal returns; (2) toptier advisors are neither significantly associated with higher probability of completion nor with shorter time to completion in acquisition of public targets; (3) top-tier advisors can indeed identify deals with larger synergies, butthey fail to appropriate them to the bidder firm; (4) top-tier advisors received higher fees on U.S. deals than non-top-tier advisors would have demanded for the same deals; (5) when considering the largest deals (Mega Deals), after 2001 it is found no support for the top-tier advisors superiority neither in U.S. nor in cross border deals.